Contractual Savings Institutions and Banks' Stability and Efficiency - Impavido, Gregorio (World Bank, Washington, DC, 2014)
The authors analyze the relationship between the development of contractual savings institutions and banks' efficiency, credit, and liquidity risks. They discuss the potential mechanisms through which the development of contractual savings institutions may affect the banking sector. They show that the development of contractual savings institutions has a significant impact on bank spreads and loan maturity. After controlling for banks' characteristics, macroeconomic factors, and more standard indicators of financial development, they show that the development of contractual savings institutions is associated with increased efficiency of the banking system and greater resilience to credit and liquidity risks.